2016
DOI: 10.1089/pho.2015.4044
|View full text |Cite
|
Sign up to set email alerts
|

Histological Effects of Er:YAG Laser Irradiation with Snoring Handpiece in the Rat Soft Palate

Abstract: The present study indicates that Er:YAG laser irradiation with snoring handpiece (PS04) causes acute shrinkage of the mucosa. This contraction decreases gradually but is still present at the end of fifth week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…21,22 The same is true for other appliances, yet what they compensate for on the discomfort front, they lose on effectivity, while invasive methods should always be considered as a last-line-of-defense option. [15][16][17]19,20 Based on the findings of this study and in addition to the findings of previous studies, [25][26][27][28][29][30][31][32][33][34][35][36][37] NightLase LAUP could potentially fill the existing gap and offer to the field of SDB a new treatment option. As it is entirely noninvasive, the mucosa remains intact, which reduces the possibility of complications.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…21,22 The same is true for other appliances, yet what they compensate for on the discomfort front, they lose on effectivity, while invasive methods should always be considered as a last-line-of-defense option. [15][16][17]19,20 Based on the findings of this study and in addition to the findings of previous studies, [25][26][27][28][29][30][31][32][33][34][35][36][37] NightLase LAUP could potentially fill the existing gap and offer to the field of SDB a new treatment option. As it is entirely noninvasive, the mucosa remains intact, which reduces the possibility of complications.…”
Section: Discussionmentioning
confidence: 76%
“…Uncertain outcomes and possible complications after uvulopalatopharyngoplasty (UPPP) procedures have led to the development of a minimally invasive version of laser-assisted uvulopalatoplasty (LAUP), used for treatment of snoring and OSA, which focuses on shrinking of the palatal tissue instead of surgically removing it. 23,24 The ''palatal stiffening'' LAUP focuses on thermally processing the relaxed soft palate, resulting in favorable fibrosis and/or collagen shrinkage and development of new collagen fibers, 25 thus producing the desired shortening and stiffening of the soft palate. This is an outpatient procedure, during which erbium-doped yttrium aluminum garnet (Er:YAG) laser is delivered to the tissue with energy densities below the ablation threshold, typically requiring no anesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect could be a result, initially, of shrinking of collagen fibers of treated area and then of the formation of new collagen fibers resulting in a remodeling of oropharynx space ( 16 - 21 ). The shrinkage of collagen tissue was also demonstrated in a histologic study of the soft palate of 20 rats submitted to a non-surgical Er:YAG laser procedure ( 22 ).…”
Section: Discussionmentioning
confidence: 90%
“…When we analyse Mallampati and Friedman classifications at one month after the treatment a significant decrease in scores were noted which could suggest that an increase in oropharynx airspace was obtained for these patients. We acknowledged that these classifications could be subjective and affected by several conditions, but other studies have shown an increase in oropharynx airflow after non-ablative Er:YAG laser procedure in human and lab studies ( 11 , 22 ). Lee and Lee ( 11 ) in a pilot study with 7 patients using cone beam computed tomography reported an increase in the mean total airway volume 12 weeks post-laser treatment.…”
Section: Discussionmentioning
confidence: 99%